Decoration of graphene-carbon nanotube nanostructures: synthesis and applications - Hu, Chenxi (2021)
Nanomaterials have played increasingly important roles in our lives with the development of modern science and technology. The design and synthesis of advanced nanomaterials have become the priorities to keep pace with the increasing demands of modern society. Carbon materials, which are made up of a broad array of allotropes, have played unique roles in numerous fields, especially the 1D carbon nanotubes (CNTs) and 2D graphene. Since the discovery of CNTs and graphene, an increasing number of experiments have been carried out on nanostructured CNTs, graphene and their roles as fillers in composites. CNTs and graphene have been regarded as promising materials, exhibiting exceptional mechanical, electrical and thermal properties, and have become a popular research topic. In this research, the major aim is to prepare well-dispersed CNT - graphene oxide (GO) based nanostructures to utilise the properties of CNT and GO. To achieve this aim, different strategies, including the freeze-drying and molecular-level-mixing (MLM) methods, have been investigated. The obtained samples were then explored for potential applications (such as thermal management and dye removal materials). In the first stage, a freeze-drying approach is introduced to prepare the well-dispersed 3D GO-CNTs (GNT) hybrid nanostructures. After that, metal nanoparticles (Cu, Ag and Ni) have been decorated on the GNT hybrid nanostructures through the molecular-level-mixing (MLM) method and subsequent reduction process. By adjusting the preparation parameters (i.e., reduction temperatures, durations and atmosphere), the results showed that metal nanoparticles were uniformly decorated on the GNT nanostructures. Meanwhile, the decorated metal nanoparticles could act as the spacers in reducing the agglomeration of graphene or CNTs. The Ag and Ni nanoparticle decorated GNT nanostructures were explored as fillers in the poly(ether ether ketone) (PEEK) and epoxy matrix, respectively. The freeze-dried Ag-GNT (FGAg) nanostructures were dispersed in the PEEK matrix, and the obtained composites exhibited enhanced thermal conductivity (ca. 1.62 times compared to pure PEEK) and significantly improved electrical conductivity (from 10-10 Ω m-1 of pure PEEK to 10-1 Ω m-1 of FGAg-PEEK composite) and better thermal durability even above the melting temperature of PEEK. The improvements can be ascribed to the 3D network generated by the FGAg nanostructures in the PEEK matrix. Similarly, the Ni-GNT (FGNi) nanostructures formed 3D aligned pathways in the epoxy matrix with the assistance of a magnetic field, which effectively enhanced the thermal (from 0.137 W m-1K-1 to the highest 0.462 W m-1K-1) and electrical (from around 1010 to 4.6×105 Ω m-1) conduction. The additional benefit was to prevent the thermal expansion of the epoxy matrix. The freeze-dried Cu-GNT (FGCu) nanostructures were explored as fillers in a Cu matrix. The FGCu-Cu pellet obtained through the spark plasma sintering demonstrated that the graphene-layer structure of FGCu samples became horizontally distributed in the matrix. However, the measured thermal conductivity of the FGCu-Cu pellet, which was in the vertical direction, was lower than pure Cu pellets (237.78 W m-1 K-1 to 360 W m-1 K-1 ). It can be predicted that there is a great potential for thermal conduction performance in the horizontal direction. The dye removal performances of the GNT based products were then investigated. The well-dispersed 3D GNT nanostructures acted as the absorbents to react with both cationic (RhB) and anionic (MO) dyes. The results showed that both RhB and MO dyes could be adsorbed, and the best adsorption capacity was found to be 248.48 mg g-1 for RhB and 66.96 mg g-1 for MO. The FGNi nanostructures exhibited excellent dye removal performance through a synergistic effect of physical adsorption and photodegradation under UV irradiation. The FGNi samples displayed a removal capacity of 41.5 mg g-1 in 5 ppm RhB solution, which outperformed the most reported Ni/C products. Meanwhile, the FGNi samples were easily collected after the reaction through magnetic separation technology. The well-dispersed GNT nanostructures and their metal nanoparticle (Ag, Ni And Cu) decorated nanostructures have been prepared via the freeze-drying method with subsequent MLM and reduction processes. The obtained products have demonstrated enhanced performances not only acting as fillers in different matrices but also applying as dye removal materials. Therefore, this research work has displayed several positive results, and such products with unique structures have shown great potential as candidates in numerous fields.